2018
DOI: 10.1029/2018je005644
|View full text |Cite
|
Sign up to set email alerts
|

Ice in Micro Cold Traps on Mercury: Implications for Age and Origin

Abstract: Evidence in radar, reflectance, and visible imagery indicates that surface and subsurface water ice is present inside permanently shadowed regions in the north polar region of Mercury. The origin of this ice and the time at which it was delivered to the planet are both unknown. Finding the smallest, most easily eroded ice deposits on Mercury can help answer these questions. Here we present evidence for volatiles trapped in cold traps of scales ∼ 1-10 m. We consider two possible delivery methods for these depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…Thermal modeling by Rubanenko et al () hypothesized the presence of “microcold trap” surface ice deposits existing in submeter regions of permanent shadow that may only be a few decimeters thick. The relative efficiency of gardening in ice makes these small unprotected deposits particularly vulnerable and we predict that if they exist, micro cold trap ice deposits would be thoroughly gardened over 10 Myr timescales (Figure c).…”
Section: Discussionmentioning
confidence: 99%
“…Thermal modeling by Rubanenko et al () hypothesized the presence of “microcold trap” surface ice deposits existing in submeter regions of permanent shadow that may only be a few decimeters thick. The relative efficiency of gardening in ice makes these small unprotected deposits particularly vulnerable and we predict that if they exist, micro cold trap ice deposits would be thoroughly gardened over 10 Myr timescales (Figure c).…”
Section: Discussionmentioning
confidence: 99%
“…at the same scale, making them good statistical analogs for thermal models (e.g., Davidsson et al, 2015;Rubanenko & Aharonson, 2017;Rubanenko et al, 2018). We constrain the impact of this assumption on our results in section 3.1.…”
Section: Basic Assumptionsmentioning
confidence: 96%
“…In all of the following derivations we assume surface slopes are distributed Gaussian. Even though the slope distribution of realistic surfaces is often non‐Gaussian (see Figure 1b and Rosenburg et al, 2011), the temperature distribution of Gaussian surfaces at some scale closely follows that of the realistic lunar topography at the same scale, making them good statistical analogs for thermal models (e.g., Davidsson et al, 2015; Rubanenko & Aharonson, 2017; Rubanenko et al, 2018). We constrain the impact of this assumption on our results in section 3.1.…”
Section: Models and Theorymentioning
confidence: 96%
“…Estimates of Mercury's water‐ice inventory range from ~10 16 to 10 18 g (Deutsch et al, ; Eke et al, ; Lawrence et al, ; Moses et al, ; Susorney et al, ). Recent studies have suggested that additional water‐ice reserves may exist in small‐scale cold traps distributed across rough, intercrater terrain in the polar regions (Deutsch et al, ; Neumann et al, ; Rubanenko et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of Mercury's water-ice inventory range from~10 16 to 10 18 g (Deutsch et al, 2018;Eke et al, 2017;Lawrence et al, 2013;Moses et al, 1999;Susorney et al, 2017). Recent studies have suggested that additional water-ice reserves may exist in small-scale cold traps distributed across rough, intercrater terrain in the polar regions Neumann et al, 2017;Rubanenko et al, 2018). enhancements has been found at the lunar poles (e.g., Colaprete et al, 2010;Fisher et al, 2017;Hayne et al, 2015;Schultz et al, 2010), the inferred concentrations of water ice are significantly lower than, and distribution of water-ice patchier than, those at Mercury (e.g., Lawrence, 2017).…”
Section: Introductionmentioning
confidence: 99%